Exploiting legal fictions in circumventing legitimate rights in marital property - Abous, Meryem; Aziz, Nor Azmawati Abdul (Linguistics and Culture Review, 2021)
The Marriage is the norm of life and living in the family’s embrace under the shade of affection and tranquility is a goal that everyone who takes this step seeks, and the happiness and balance of the family can only be achieved by obtaining what can be achieved from the requirements of a decent life.But not everything that a person wishes to realize, some have intervened Factors and inconveniences make married life impossible to continue, and the most important of these factors, according to a scientific study, is money According to ourIslamic law, the offspring must be legitimate, and this will not happen except through legal marriage, and in the verse it is associated. Money with children because it has a strong influence and a close link to married life, which in turn is considered a partnership between two parties. The spouses may not be successful in completing this partnership, and the matter ends in divorce, and often the woman is forced to demand her legal and material rights. In this research, I will discuss, in particular, the tricks that some lawyers use to make things difficult, or to prevent the divorced woman from having her rights, especially material ones.